Micro/nano microfiber synthetic leather base with different nanofiber diameters. (February 2021) - Duo, Yongchao; Qian, Xiaoming; Zhao, Baobao; Qian, Yao; Xu, Ping; Qi, Jingjing
The microfiber synthetic leather base (MSLB) was prepared by mixing hollow segmented pie microfibers and polyacrylonitrile electrospun nanofibers. Micro/nano hybrid leather base was prepared to simulate the three-dimensional (3D) structure of natural leather. The diameter of the polyacrylonitrile nanofibers was 950 nm, 450 nm and 200 nm, respectively. The effects of nanofibers of different diameters on the performances of MSLB were investigated. The results indicated that polyacrylonitrile nanofibers were randomly dispersed in MSLB. Differential scanning calorimetry further demonstrated the presence of polyacrylonitrile nanofibers in MSLB, and thermogravimetric analysis showed that the addition of polyacrylonitrile nanofibers had a little influence on the thermal stability of MSLB. There was no significant change in the water contact angle of the MSLB surface before and after the addition of nanofibers. As the diameter of the nanofibers decreased from 950 nm to 200 nm, the static water vapor transmission rate was increased by 28.2%, the softness was increased by 39.74%, and air permeability was decreased by 17.16%. When the nanofiber diameter is 950 nm, the moisture absorption performance of MSLB was better, which was 768.99%. Moreover, the tear strength was also significantly enhanced by 105.76%.